AN ANALYSIS OF TESTS DESIGNED BY ISLAMIC EDUCATION TEACHERS BASED ON HIGHER-ORDER THINKING SKILLS - Sakban, Wahyu; Nurmawati, Nurmawati; Haidir, Haidir (UIN Sumatera Utara Medan, 2023)
This study aims to analyze the quality and quantity of the PAI (Islamic Education) tests based on Bloom's taxonomy. The research was conducted at SMP Tarbiyah Islamiyah in Hamparan Perak. This research is qualitative research with a descriptive approach. Primary data sources are Islamic Education teachers and Mid-term tests for Islamic Education subjects, while secondary data sources are from literature studies and previous studies. Data collection instruments are documentation and interviews. The research findings indicated that the analysis of the quality of the items on the reliability aspect shows a reliability coefficient of 0.959 in the reliable category. Distractor analysis showed a functioning distractor at 25 questions or 71.43% and a malfunctioning distractor at 10 questions or 28.57% and analysis of the quality of the items according to Bloom's taxonomy in the cognitive domain. Therefore, from 35 multiple-choice items, it was found that 51.43% were in the HOTS category and 48.57% were included in the LOTS item category.